2012
DOI: 10.3791/4193
|View full text |Cite
|
Sign up to set email alerts
|

A Galvanotaxis Assay for Analysis of Neural Precursor Cell Migration Kinetics in an Externally Applied Direct Current Electric Field

Abstract: The discovery of neural stem and progenitor cells (collectively termed neural precursor cells) (NPCs) in the adult mammalian brain has led to a body of research aimed at utilizing the multipotent and proliferative properties of these cells for the development of neuroregenerative strategies. A critical step for the success of such strategies is the mobilization of NPCs toward a lesion site following exogenous transplantation or to enhance the response of the endogenous precursors that are found in the perivent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Some studies have indicated that direct current electrical fields or electrical stimulation enhance migratory ability of various type of cells like NSCs and MSCs in vitro [13-15]. In the present study, BMSCs implanted in the contralateral corpus callosum migrated towards the epidural cathode electrode.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some studies have indicated that direct current electrical fields or electrical stimulation enhance migratory ability of various type of cells like NSCs and MSCs in vitro [13-15]. In the present study, BMSCs implanted in the contralateral corpus callosum migrated towards the epidural cathode electrode.…”
Section: Discussionsupporting
confidence: 54%
“…There are some reports that electric fields may direct various types of cells in vitro [13-15]. Furthermore, electrical stimulation enhances migration of endogenous neural stem cells and cell proliferation in vivo [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other galvanotaxis chamber designs made in culture dishes 27,28 , there are several benefits to the current design. First, the glass surface is suitable for imaging and the coverglass with cells can be retrieved after galvanotaxis for immunostaining.…”
Section: Assembling Galvanotaxis Chambersmentioning
confidence: 99%
“…Third, the modified platinum electrodes are inert in the electric field. Compared to the silver electrodes as used in other galvanotaxis methods 27 , they do not break down or release metal ions to the medium, which reduces the cytotoxicity in galvanotaxis. Fourth, we may change the intervals of frame capturing, which helps us to monitor either fast or slow cell migration.…”
Section: Assembling Galvanotaxis Chambersmentioning
confidence: 99%
“…New technologies such as microfluidic chambers (1318), capillary techniques (19,20), galvanotaxis assay (2123), Radius CytoSelect Cell Migration Assay (24), electric cell substrate impedance sensing (ECIS) assay (25), scratch-wound assay (26), gap closure assay (27), and 3-D collagen/fibrin gels (28,29) have been developed to provide more in vivo–like conditions to assess a wide array of motility mechanisms. Most of these systems assess only one substrate at a time or depend on the adsorption capacity of the glass or the dispersion capacity of ink-jet printer nozzles (30,31).…”
mentioning
confidence: 99%